2018
DOI: 10.20945/2359-3997000000055
|View full text |Cite
|
Sign up to set email alerts
|

Waist circumference measurement sites and their association with visceral and subcutaneous fat and cardiometabolic abnormalities

Abstract: Objectives: To estimate the degree of variability of the waist circumference (WC) when obtained in different anatomical sites and compare the performance of the measurement sites as predictors of visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) and cardiometabolic abnormalities. Subjects and methods: Cross-sectional study involving 119 individuals with overweight (50.3 ± 12.2 years), in which six WC measurement sites were evaluated (minimal waist, immediately below the lowest rib, midpoint b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 35 publications
(52 reference statements)
3
26
0
1
Order By: Relevance
“…Some results revealed that WC is a better indicator of visceral fat and CVD risk compared with BMI and waist to hip ratio. The results of this study showed the same result 2426. A previous study showed that the V/S ratio assessed by ultrasonography is significantly associated with glucose metabolism in patients at high risk of developing type 2 diabetes mellitus 27.…”
Section: Discussionsupporting
confidence: 84%
“…Some results revealed that WC is a better indicator of visceral fat and CVD risk compared with BMI and waist to hip ratio. The results of this study showed the same result 2426. A previous study showed that the V/S ratio assessed by ultrasonography is significantly associated with glucose metabolism in patients at high risk of developing type 2 diabetes mellitus 27.…”
Section: Discussionsupporting
confidence: 84%
“…In our study, we cannot assert that the anatomical location could affect the calculation of RFM. Nonetheless, a study in overweight adults in Brazil found a difference of 3.2 cm in WC in men, measured at the umbilical level and immediately above the iliac crest, while in women the difference was only 0.1 cm [44]. Also, a study in older adults measured WC at ten different sites in relation to abdominal fat by DXA and found that the association was practically identical [45].…”
Section: Discussionmentioning
confidence: 99%
“…But WC is indeed genderspeci c (36). Furthermore, as Bosy-Westphal A et al and Pinho CPS et al postulated, it was noted that the WC, regardless of the measurement site, was predominantly a subcutaneous fat index among women (37,38). Moreover, Pinho CPS et al (38) proposed that the distribution of abdominal fat was heavily genderdependent.…”
Section: Discussionmentioning
confidence: 98%